A clinical evaluation of 23 glass ionomer cement restorations placed in 1997, 1998 and 1999 - Lingat, Ethel D.; Atienza, Angelina A. (Adviser).
In the study, 14 subjects with 23 Glass Ionomer Cement (GIC) restorations were examined. A score criteria was used to determine whether the restoration survived or failed. The defects present were measured against the 0.5 mm ball of a Community Periodontal Index (CPI) probe. Among the GIC restored teeth, 8 were placed in 1997 (>2 years), 12 in 1998 (1 year - <2 years), and 3 in 1999 (6 months - <1 year). Enclosed in the parentheses were the period from the time the GIC was placed up to the time that it was evaluated. The results indicate a consistent low survival percentage for the three time periods. But surprisingly, the >2 years group had the highest survival percentage, which was 37.5. The survival percentage in the 1 year - <2 years was 25, while that of the 6 months - <1 year was 33. It is therefore concluded, that majority of the GIC restorations performed on the 14 grade 4 students from Pinyahan Elementary School are considered failed restorations.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Atraumatic Restorative Treatment (ART).